Pengaruh Suku Bunga Kredit, Kurs Dollar Amerika Serikat dan Indeks RCA Terhadap Volume Ekspor Udang Segar (HS92-030623) Indonesia ke Beberapa Negara Periode 1999-2012 - Putri Maharani, Desak Putu; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
Indonesia has vast and potential territorial waters in the field of fisheries. With the existence of such potential, the author had the idea to conduct research on that, specifically about Indonesian export commodities of fresh shrimp to several countries. This research determine the effect of independent variables simultaneously and partially to Indonesia’s export volume of Fresh Shrimp (HS92 - 030 623) to some countries during period 1999-2012 and the most dominant variable that effect the export volume of fresh shrimp. This research applied multiple linear regression analysis. The simultaneously (F-test) results: In Japan and Singapore, all three independent variables have significant effect on the volume of exports of fresh shrimp, whereas no effect in Malaysia. The partially (t-test) results are: RCA indices have significant effect on Japan and Singapore, while it has no effect on Malaysia. Mortgage interest rates and the U.S. dollar exchange rate do not affect the export volume of fresh shrimp in all three countries. The most dominant variable is the RCA index for Japan and Singapore, while in Malaysia is interest rate for the loan.
Keywords: Export Volume; Interest Rate; American Dollar; RCA Index